Penerapan Metode Design Thinking Pada Perancangan UI/UX Sistem Informasi Penelitian Mahasiswa Berbasis Web - Arizona Firdonsyah; Zahra Arwananing Tyas; LM Ma'rifatun (INFORMAL: Informatics Journal, 2023)
Advances in technology provide opportunities to increase efficiency in various sectors, including the licensing process and the operations of government agencies. The Bantul District Health Office, as a health and research service provider, still relies on a semi-manual research licensing process. To overcome this, a structured research licensing information system is needed on a website basis. The stages of making a website start with UI/UX design. This study designed a UI/UX system using the Design Thinking method. The Empathize stage involves interviews and observations to understand the needs of users, especially the Head of the Health Office Program Subdivision. The Define phase identifies core requirements such as a list of user requirements, business process flowcharts, and the use of Figma for design and prototyping. The Ideate Stage involves brainstorming and wireframes, while the Prototype Stage produces the final design for testing. The Test phase involved Usability Testing, with fixes such as changing the message feature to notifications and adding the option to sign in with a Google account. The results showed that the prototype answered the problems of the Bantul District Health Office in designing the SIPENA UI/UX according to user needs.